2021
DOI: 10.1002/erv.2875
|View full text |Cite
|
Sign up to set email alerts
|

Autistic characteristics in eating disorders: Treatment adaptations and impact on clinical outcomes

Abstract: Objective: Autistic people with eating disorders (EDs) may have special needs that are not met in standard ED treatment, raising the need for treatment adaptations to accommodate co-existing autism spectrum condition (ASC).Little is currently known about the nature of existing treatment options or adaptations for this population. We conducted a pre-registered systematic review to: (1) identify research articles describing existing interventions for patients with ED and comorbid ASC, and to critically review ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…In the same vein, in the field of eating disorders (ED), cross-sectional studies have documented that those who report more autistic features present more severe ED psychopathology and complex illness profiles, with more comorbid anxiety, depression, and OCD symptoms ( 22 , 23 ). Furthermore, previous longitudinal, naturalistic studies of AN patients admitted to inpatient ED services found that those who self-reported higher levels of autistic features also reported more ED symptoms, depression and anxiety, and poorer social functioning at both admission and discharge ( 24 26 ). However, notably the average duration inpatient treatment was 16 weeks making it difficult to draw long-term conclusions from these findings.…”
Section: Introductionmentioning
confidence: 90%
“…In the same vein, in the field of eating disorders (ED), cross-sectional studies have documented that those who report more autistic features present more severe ED psychopathology and complex illness profiles, with more comorbid anxiety, depression, and OCD symptoms ( 22 , 23 ). Furthermore, previous longitudinal, naturalistic studies of AN patients admitted to inpatient ED services found that those who self-reported higher levels of autistic features also reported more ED symptoms, depression and anxiety, and poorer social functioning at both admission and discharge ( 24 26 ). However, notably the average duration inpatient treatment was 16 weeks making it difficult to draw long-term conclusions from these findings.…”
Section: Introductionmentioning
confidence: 90%
“…The association appears to be strongest with anorexia nervosa (AN), but also other EDs (OED) such as bulimia nervosa and binge‐eating disorder are overrepresented in individuals with autism, as are weight extremes (underweight and obesity) (Nickel et al., 2019; Sedgewick et al., 2020; Westwood & Tchanturia, 2017). Among individuals with ED, those with co‐occurring autism are often considered to have more severe and enduring ED presentations (i.e., poorer prognosis), and efforts have been made to adapt ED treatment specifically to the needs of individuals with co‐occurring autism (Li et al., 2021; Tchanturia et al., 2020). However, the evidence supporting the association of autism with increased ED severity is marked by weak findings and contradictory results, which we will summarise below.…”
Section: Introductionmentioning
confidence: 99%
“…In this special issue, several manuscripts which are reviewed address the subjects of: screening for autism (Adamson et al., 2022; Carter Leno et al., 2022), understanding of recovery from EDs (Sedgewick et al., 2021), and how autism and ED comorbidity affects treatment outcomes (Li et al., 2021). Also covered are: patients’ experiences of treatment and clinical services (Babb et al., 2022) and how sensory processing and eating behaviours are related in autism (Nimbly et al., 2022).…”
Section: What Do the Main Stakeholders Think?mentioning
confidence: 99%